MENYUSUN KEMISKINAN: BAGAIMANA RASISME MEMBENTUK ANAK KEMISKINAN DAN KESEHATAN ANAK DAN REMAJA - Novriansyah, Beldi; Surya, Edi; Destriani, Mellanie; Hendri, Taufik; Untung, DB.; Nelly, Nelly; Suryadi, Suryadi; Fikri, KMS. Novyar Satriawan (Yayasan Education and Social Center, 2025)
The most severely affected racial and ethnic groups by poverty are the Black, Native, and Latinx populations. The disproportionate distribution of poverty should be recognized as a result of governmental decisions, some of which have endorsed violence, while others have established norms that persistently influence access to power, resources, rights, and safeguards. This review utilizes interdisciplinary scholarship from pediatrics, public health, environmental health, epidemiology, social and biomedical sciences, law, policy, and urban planning to investigate the primary subject. What is the correlation among structural racism, poverty, and pediatric health? We examine historical and contemporary events essential for comprehending poverty within the framework of American racism and pediatric health. We contest traditional frameworks that regard racialized poverty as an intrinsic aspect of American society. We propose a conceptual framework to demonstrate how white supremacy and American capitalism perpetuate structural racism and influence the racial allocation of resources and power in the environments where children and adolescents reside, learn, and engage in recreational activities, thereby exacerbating pediatric health disparities. We provide antipoverty techniques rooted in antiracist practices that address the cumulative, generational effects of racism and poverty on health to enhance the well-being of children, adolescents, and families.